Conceptualization of hypersituation as result of IoT in education - Moreira, Filipe T. (2020)
With the emergence of new technologies and their use in different areas, new experiences emerge. In the context of the use of IoT in educational contexts, the potential of hypersituation has been considered by several authors as the greatest potential of these technologies for this field of study. However, despite several references to this fact, this term still lacks further conceptualization and the drawing of guidelines to achieve it. Thus, this paper aims to present an interpretation and definition of the term hypersituation indicating potentials, challenges, and ways to achieve it.